2012
DOI: 10.7314/apjcp.2012.13.9.4561
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Treatment for Pain Among Cancer Patients by Rational-Emotive Behavior Therapy - Efficacy in both India and Iran

Abstract: The aim of the present study is to find out the influence of rational-emotive behavior therapy (REBT) on pain intensity among cancer patients in India and Iran. The study followed a quasi-experimental, pre-post test, carried out with a sample of 88 cancer patients, aged 21-52 years, referred to the Baharat cancer hospital of Mysore in India and Shahidzade hospital of Behbahan in Iran. They were randomly assigned to the experimental (n=India 21; Iran 22) and control (n=India 22; Iran 23) groups. Pain was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…Anticancer treatment, symptomatic pain control, rehabilitation, and psychiatric support are the essential elements of the treatment for the patient with cancer pain (Mahigir et al, 2012).…”
Section: Pain Managementmentioning
confidence: 99%
“…Anticancer treatment, symptomatic pain control, rehabilitation, and psychiatric support are the essential elements of the treatment for the patient with cancer pain (Mahigir et al, 2012).…”
Section: Pain Managementmentioning
confidence: 99%
“…It is important to note that the psychological treatment of patients with tumor using REBT cannot be overstated. A 2012 randomized controlled trial by Mahigir et al[5] found that REBT was effective in decreasing pain intensity scores of patients with cancer in two countries – India and Iran. It is against this backdrop that this article sheds light on the findings of the study by the researchers at University of Nigeria Nsukka.…”
Section: Introductionmentioning
confidence: 99%
“…REBT offers enduring change in 1 to 20 sessions of cognitive therapies with approximately 50 minutes weekly individual sessions. 27 This study has the following strengths. This is the first study of its kind analysing the effect of REBT in chronic headache and musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%